2010
DOI: 10.1007/s11738-010-0679-3
|View full text |Cite
|
Sign up to set email alerts
|

Different antioxidant responses to salt stress in two different provenances of Carthamus tinctorius L.

Abstract: Seedlings of two Tunisian Carthamus tinctorius L. provenances (Kairouan and Tazarka) differing in salt sensitivity were hydroponically grown at 0 and 50 mM NaCl over 21 days. Leaves of Kairouan (saltsensitive) showed a 48% restriction in their growth at 50 mM NaCl although they accumulated less sodium than those of Tazarka (less salt-sensitive) that maintained an unchanged growth. Salt treatment induced oxidative stress in C. tinctorius and the effect was more pronounced in the leaves of the more salt sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 57 publications
2
19
1
Order By: Relevance
“…According to [31], the drastic effect of salinity (75 mM) on TPC of Salvia sclarea L. may be due to a less efficient ROS as a result of an imbalance between ROS and antioxidant formation, leading to the installation of the oxidative stress. However, this trend is contradictory to that observed in cucumber [46], Carthamus tinctorius [47,48], Salvia officinalis [30], and Origanum majorana , Zn 2+ contents (µg/g DW) of M. vulgare subjected to different NaCl concentrations (0, 25, 50 and 100 mM) during 5 months. [49].…”
Section: Total Phenolic Contentcontrasting
confidence: 70%
“…According to [31], the drastic effect of salinity (75 mM) on TPC of Salvia sclarea L. may be due to a less efficient ROS as a result of an imbalance between ROS and antioxidant formation, leading to the installation of the oxidative stress. However, this trend is contradictory to that observed in cucumber [46], Carthamus tinctorius [47,48], Salvia officinalis [30], and Origanum majorana , Zn 2+ contents (µg/g DW) of M. vulgare subjected to different NaCl concentrations (0, 25, 50 and 100 mM) during 5 months. [49].…”
Section: Total Phenolic Contentcontrasting
confidence: 70%
“…Elevated CO 2 mitigates the oxidative stress caused by salinity, involving lower ROS generation and a better maintenance of redox homeostasis as a consequence of higher assimilation rates and lower photorespiration [243]. Salinity-induced ROS disrupt normal metabolism through lipid peroxidation, denaturing proteins, and nucleic acids in several plant species [12,242,244]. Differential genomic and proteomic screenings carried out in Physcomitrella patens plants showed that they responded to salinity stress by upregulating a large number of genes involved in antioxidant defense mechanism [245] suggesting that the antioxidative system may play a crucial role in protecting cells from oxidative damage following exposure to salinity stress in P. patens.…”
Section: Salinitymentioning
confidence: 99%
“…Thus, as a traditional viewpoint, phenolic compounds are defined as secondary antioxidants, and play an assisting role in detoxifying ROS, when the primary antioxidant system is depressed under severe stress (Fini et al, 2011). However, this traditional viewpoint has been challenged recently, because moderate saline stress is more liable to induce accumulation of phenolics in plants without severe oxidative stress and depression of antioxidant system (Abrol et al, 2012;Karray-Bouraoui et al, 2010;Ksouri et al, 2007;Shao et al, 2015;Zhao et al, 2015). Therefore, the relation between antioxidant system and phenolic metabolites in resisting oxidative stress is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese, honeysuckle is a traditional medicinal plant, and has been widely used in healthcare, food and cosmetics industries. At present, studies attach importance to salt-induced changes in concentrations of bioactive phenolic compounds in medicinal plants (Colla et al, 2013;Karray-Bouraoui et al, 2010;Shao et al, 2015;Zhao et al, 2015). However, antioxidant mechanisms of phenolics in vivo are often overlooked, and the relation between accumulation of phenolics and antioxidant system induction under saline stress is less concerned.…”
Section: Introductionmentioning
confidence: 99%